The world of Elizabeth Inchbald : essays on literature, culture, and theatre in the long eighteenth century - Ennis, Daniel James, 1970-; Johnson, E. Joe (Edward Joe); Anderson, Misty G., 1967-; Bowden, Martha F.; Choudhury, Mita; Craig, Robert; Gerard, W. B.; Graves, Randa; Kairoff, Claudia Thomas; Lowenthal, Cynthia J. (University of Delaware Press, 2022)
"This collection centers on the remarkable life and career of the writer and actor Elizabeth Inchbald (1753-1821), active in Great Britain in the late eighteenth century. Inspired by the example of Inchbald's biographer, Annibel Jenkins (1918-2013), the contributors explore the broad historical and cultural context around Inchbald's life and work, with essays ranging from the Restoration to the nineteenth century. Ranging from visual culture, theater history, literary analyses, to historical investigations, the essays not only present a fuller picture of cultural life in Great Britain in the long eighteenth century, but also reflect a range of disciplinary perspectives. The collection concludes with the final scholarly presentation of the late Professor Jenkins, a study of the eighteenth-century English newspaper The World (1753-1756)"--